2022
DOI: 10.3390/biomedicines10112982
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aβ40 and Aβ42 Fibrils on the Transcriptome of Primary Astrocytes and Microglia

Abstract: Fibrillar amyloid β-protein (Aβ) deposits in the brain, which are primarily composed of Aβ40 or Aβ42 peptides, are key pathological features of Alzheimer’s disease (AD) and related disorders. Although the underlying mechanisms are still not clear, the Aβ fibrils can trigger a number of cellular responses, including activation of astrocytes and microglia. In addition, fibril structures of the Aβ40 and Aβ42 peptides are known to be polymorphic, which poses a challenge for attributing the contribution of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…The ITC experiments we have performed in this work point to this being a selective and saturable interaction that is energy requiring and hence possibly deliberate and important for cellular physiology and/or pathology. Aβ peptide binding to EVs detected using ITC unveiled that, while Aβ40 binding was endothermic and saturable, the more aggregation prone Aβ42 [83][84][85], was peptide-form dependent, with endothermic heat exchanges more robustly observed when preformed fibrillar Aβ42 (Aβ42F) was added to the assay. Thus, our ITC experiments suggest a preference for binding to fibrillar vs. monomeric forms of Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…The ITC experiments we have performed in this work point to this being a selective and saturable interaction that is energy requiring and hence possibly deliberate and important for cellular physiology and/or pathology. Aβ peptide binding to EVs detected using ITC unveiled that, while Aβ40 binding was endothermic and saturable, the more aggregation prone Aβ42 [83][84][85], was peptide-form dependent, with endothermic heat exchanges more robustly observed when preformed fibrillar Aβ42 (Aβ42F) was added to the assay. Thus, our ITC experiments suggest a preference for binding to fibrillar vs. monomeric forms of Aβ42.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with brain amyloidosis and normal cognition exhibited higher levels of CSF Aβ42 than did those with MCI or AD, suggesting that higher levels of CSF Aβ42 were associated with preserved cognitive function in individuals with brain amyloidosis [203]. Microglia treated with Aβ42 fibrils exhibited upregulated gene expression compared to those treated with Aβ40 fibrils.…”
Section: Aβ42/40mentioning
confidence: 97%
“…The study reported different toxic effect of polymorphic Aβ fibril morphologies on primary rat embryonic hippocampal neurons with Aβ fibrils grown under quiescent conditions having higher toxicity than those grown under agitated conditions (Petkova et al, 2005 ). At the in vivo level, studies showed differential neuropathological effects in transgenic mouse models injected with distinct polymorphic Aβ fibrils, including Aβ fibrils extracted from familial and sporadic AD cases, as well as synthetically produced Aβ fibrils with distinct C‐terminal variants (Ruiz‐Riquelme et al, 2021 ; Stöhr et al, 2014 ; Watts et al, 2014 ; Zhu et al, 2022 ). Synthetic Aβ fibrils injected into mice have been shown to be less potent in inducing Aβ deposition compared with brain‐derived fibrils (Stöhr et al, 2012 ).…”
Section: Structural Polymorphism Of Synthetic and Brain‐derived ...mentioning
confidence: 99%